Kuantifikasi Objek Jual-Beli dalam Transaksi Borongan di Kota Metro: Perspektif Hukum Islam: Kuantifikasi Objek Jual-Beli dalam Transaksi Borongan di Kota Metro: Perspektif Hukum Islam - Wahyudi, Ismail; Nasrudin, Muhamad; Sainul, Sainul (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
This paper discusses the problem of buying and selling brown sugar in Metro City, which in practice has several exciting things to study related to Islamic law. First, weighing brown sugar together with wooden crates that have different weights. Second, weighing brown sugar using samples or samples. This paper focuses on discussing how Islamic law views the practice of considering brown sugar in Metro City. This phenomenon is studied using qualitative research and a case study approach. The data were obtained using field observation techniques, interviews with traders as sources, then analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results showed that the practice of buying and selling brown sugar in the Metro City Market fulfills the pillars and requirements of buying and selling in Islamic law. Quantification of the objects of sale and purchase in packages at Metro Market based on Islamic Economic Law (HESy) refers to the concept of ‘urf (traditional customs). This practice is included in ‘urf hasan because it is based on convenience, trust, and volunteerism between the seller and the buyer. Thus, the applicable law of weighing brown sugar in Metro City is valid (shahih).